Robustness of nonuniform polynomial dichotomies for difference equations - Barreira, Luis; Fan, Meng; Valls, Claudià; Zhang, Jimin (Topological Methods in Nonlinear Analysis, 2011)
For a nonautonomous dynamics with discrete time defined by a sequence of linear operators in a Banach space, we establish the robustness of polynomial contractions and of polynomial dichotomies under sufficiently small linear perturbations. In addition, we consider the general case of nonuniform polynomial behavior.